Carboxymethyl-botryosphaeran stabilized carbon nanotubes aqueous dispersion: A new platform design for electrochemical sensing of desloratadine - Salamanca-Neto, Carlos A.R.; Olean-Oliveira, André [UNESP]; Scremin, Jessica; Ceravolo, Graziela S.; Dekker, Robert F.H.; Barbosa-Dekker, Aneli M.; Teixeira, Marcos F.S. [UNESP]; Sartori, Elen R. (Elsevier, 2020)
The polysaccharide carboxymethyl-botryosphaeran (CMB) was used to improve the dispersion of multi-walled carbon nanotubes (MWCNTs) in water. This feature was applied in modifying a glassy carbon electrode (GCE) to construct a sensitive voltammetric sensor for the determination of desloratadine (DESL), a tricyclic antihistamine. The morphology and spectroscopic behavior of the sensor were evaluated. The modified sensor was characterized as homogeneous, and presented a higher electroactive area and a lower charge transfer resistance compared to the unmodified GCE. Using linear sweep voltammetry at 25 mV s−1, the developed sensor presented a sensitivity of 1.018 μA L μmol−1 in the linear working range of 1.99–32.9 μmol L−1, with a detection limit of 0.88 μmol L−1 of DESL in 0.10 mol L−1 potassium hydrogen-phosphate solution (pH 8.0). In addition, the sensor showed excellent repeatability with a relative standard deviation of only 1.02% for a sequence of 10 measurements. The sensor was successfully applied in the analysis of pharmaceutical preparations containing DESL, with equivalent results compared to a validated spectrophotometric method at the 95% confidence level. The sensor was also employed in the analysis of a spiked sample of DESL in rat serum.
Keywords: Biological sample; Botryosphaeria rhodina MAMB-05; Modified glassy carbon electrode; MWCNTs aqueous dispersion; Pharmaceutical analysis